As Políticas Públicas para a promoção da igualdade racial no contexto de Presidente Prudente - Silva, Ozileide Matos da [UNESP] (Universidade Estadual Paulista (Unesp), 2012)
This work aims at presenting the historical and social path traversed in Brazil since slavery until the implementation of affirmative public policies to promote racial equality, at the local level, in the municipality of Presidente Prudente-SP. Therefore, the starting point was the equal rights guaranteed by the Constitution. As a result, there was a brief historical path of national trajectory, starting from slavery to the so-called cordial racism, seeking to demonstrate the route of racial discrimination in the country. Later, we made notes about the necessity and debate on public policy statements of various fields, were made explicit in the text and the articles of the Constitution which prescribe the crime of racism and some of the situations that were highlighted in the national media. The focus in the city of Presidente Prudente was through historical research, interviews, photographic records and documents that informed about the presence of black people in the city. From these data, based on previous research, it was possible to trace the formation and development of the Black Movement in the city and thus point the way to the formation of this City Council for Racial Equality and the need for application of affirmative action policies for the municipality by hereby. Data from the 2000 Census and 2010 indicate the demand of Presidente Prudente as the percentage of blacks self-declared grew this decade. The main demands are paring the areas of Health since the rate of black women Administrative Region (RA) of Presidente Prudente who die in puerperium and high; Education through enhanced, by the Municipal Education Law No. 10,639, and due attention to african-Brazilian culture by respecting the religious manifestations of African origin among others... (Complete abstract click electronic access below)

Esse trabalho tem por finalidade apresentar o caminho histórico e social percorrido no Brasil desde a escravidão até a implantação das políticas públicas afirmativas para a promoção da igualdade racial, em esfera local, no município de Presidente Prudente- SP. Para tanto, o ponto de partida foi a igualdade de direitos, garantida na Constituição Federal. Na sequência, foi realizado um breve trajeto histórico da trajetória nacional, partindo da escravidão até o chamado “racismo cordial”, buscando demonstrar o percurso da discriminação racial no país. Posteriormente, foram feitos apontamentos sobre a necessidade e o debate em torno das políticas públicas afirmativas de diversos âmbitos, e foram explicitados no texto os artigos da Constituição Nacional que prescrevem o crime de racismo e algumas situações deste que tiveram destaque na mídia nacional. O enfoque no município de Presidente Prudente se deu por meio de uma pesquisa histórica, de entrevistas, registros fotográficos e documentos que informavam a respeito da presença do povo negro no município. A partir desses dados baseando-se em pesquisas anteriores, foi possível traçar a formação e desenvolvimento do Movimento Negro na cidade e assim, apontar o caminho deste até a formação do Conselho Municipal de Igualdade Racial e a necessidade de requerimento... (Resumo completo, clicar acesso eletrônico abaixo)
Keywords: Geografia; Politicas publicas; Racismo; Negros - Segregação; Igualdade